PENGEMBANGAN MODUL BERGAMBAR PADA MATERI SISTEM PENCERNAAN PADA MANUSIA KELAS VIII SEMESTER I UNTUK SMP - Amelia, Siti Riski; Risdawati, Renny; Fitriani, Vivi (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Many of media can be develop by the teacher in learning process. One of them is modul. Modul is a book that written in order the students can learn indenpendently. In Junior High School Students 1 Ranah Batahan is not find the use picture handbook yet, especially in System Human Digestivus subject. The purpose of this research is to produce valid a practical picture modul for System Human Digestivus. Kind of this research is research for development by using 4-D development models that modifield from Thiagarajan dan Semmel (1974 in Trianto, 2012: 94). The research in July 29 2013 to the teachers and students of Junior High School 1 Ranah Batahan.The modul include valid of score 85,63% and practical criteria to be used with practicalities score as 83,95%. So, the result of this reseach is a picture modul in System Human Digestivus valid and practical in 1stÂ semester for grade of Junior High School Students.Â